Advanced engineering physics: WBUT-2014 - Bhattacharya, Sujay Kumar (McGraw Hill, 2014)
Advanced engineering physics: WBUT-2014 / Bhattacharya, Sujay Kumar. -- New Delhi: McGraw Hill, 2014 530 B575e4 4th ed. No. of Copies : 1